Development, Democracy, and Welfare States : Latin America, East Asia, and Eastern Europe - Haggard, Stephan (Book collections on Project MUSE., 2008)
Comparing the welfare states of Latin America, East Asia and Eastern Europe, the authors trace the origins of social policy in these regions to political changes in the mid-20th century, and show how the legacies of these early choices are influencing welfare reform following democratization and globalization.